Analysis of Air Cargo Cost Efficiency at Sentani Airport Papua: The Role of Logistics Infrastructure, Tariff Policies, and Technological Innovation - Toja, Andi Batari; Bunahri, Rifqi Raza (Dinasti Publisher, 2024)
This study examines the factors influencing air cargo cost efficiency in Papua, where shipping costs are disproportionately high. The research focuses on three variables: logistics infrastructure, tariff policy, and technological innovation. A quantitative approach was applied, with data collected from 50 logistics employees at Sentani Papua Airport using a Likert scale questionnaire. Multiple linear regression analysis was used to assess the partial and simultaneous effects of these factors. The results show that logistics infrastructure and tariff policy have significant positive effects on air cargo cost efficiency, with t-test values of 6.774 and 9.972, respectively. However, technological innovation has no significant effect, with a significance value of 0.076. The F-test results indicate that the independent variables jointly influence the dependent variable, with an Fcount of 40.635, far exceeding the Ftable value of 2.81. The three factors account for 72.1% of the variation in air cargo cost efficiency, while the remaining 27.9% is influenced by other factors. This study suggests that improving logistics infrastructure and tariff policies can enhance cost efficiency, benefiting companies and consumers.